PENGARUH JENIS INDUSTRI, KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL, DAN KEPEMILIKAN ASING TERHADAP KINERJA MODAL INTELEKTUAL - Supradnya, I Nyoman Trisna; Ulupui, I Gusti Ketut Agung (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.05.TAHUN 2016, 2016)
This research aims to examine the influence of industrial type, managerial ownership, institutional ownership, and foreign ownership on intellectual capital performance. The intellectual capital performance is measured by Extended Value Added Intellectual Capital Plus (E-VAIC Plus) which was developed by Ulum (2014). Population of this research is 491 listed companies in Indonesia Stock Exchange in the years 2012-2014. The sampling was created through purposive sampling technique that resulted in 49 companies samples. Multiple regression was used to analyze the influence of the independent variables on the dependent variable. The result of multiple regression analysis shows financial industrial type of intellectual capital performance is higher than non financial industrial type of intellectual capital performance, institutional ownership and foreign ownership have positive influence on intellectual capital performance. Managerial ownership does not influence intellectual capital performance.
Keywords: intellectual capital performance, E-VAIC Plus.